Analisis Pelaksanaan Remedial pada Mata Pelajaran Al-Qur’an Hadis di MAS Hidayatul Mubtadi'ien Tapung Kampar - Hindarsyah, Wahyu Eka; Risnawati; Risqa, Miftahir (GHIROH, 2024)
This paper focuses on the remedial implementation of Al-Qur'an Hadith lessons at MAS Hidayatul Mubtadi'ien Tapung Kampar. The aim of the research is to understand how the remedial process is carried out in Al-Qur'an Hadith lessons, as well as evaluate its effectiveness in improving student understanding and achievement. The research method used is a qualitative approach with a case study as the research design. Data was collected through interviews with subject teachers and students. The research results showed that the implementation of remedial measures at MAS Hidayatul Mubtadi'ien Tapung did not have a positive impact on increasing students' understanding and achievement. At the start of the evaluation, it showed that the remedial implementation at MAS Hidayatul Mubtadi'ien Tapung was less effective, where only a few students who took part in the remedial program experienced an increase in understanding and achievement in the Al-Qur'an Hadith subject. So the implementation of the remedial program for Al Qur'an Hadith lessons is considered not to have a positive impact on the learning process.